Conflicting effects of haemolysis on plasma sodium and chloride are due to different haemolysis study protocols: A case for standardisation. (March 2022) - Kalaria, Tejas; Gill, Henry; Sharrod-Cole, Hayley; Ford, Clare; Gama, Rousseau
Background: Haemolysis has been reported as having a positive, negative or no effect on plasma sodium (PNa) and chloride (PCl). We investigated the haemoltytic effect of different haemolysis protocols on PNa and PCl using modelling and laboratory experiments. Methods: In a modelling experiment, percentage change and recovery due to dilution in routinely ( in vitro ) haemolysed samples were compared against shear stress haemolysis and samples spiked with haemolysate from whole blood freeze–thaw, packed cells freeze–thaw and osmotic shock protocols. The results were compared against a control base pool. Additionally, for the osmotic shock method, results were compared against saline- and deionised water (DIW)-spiked controls. In a laboratory experiment, percentage change and recovery were similarly compared using haemolysate from whole blood freeze–thaw and osmotic shock protocols. PNa, PCl and H-index were measured on the Abbott Architect and haemoglobin on the Sysmex XN-9000. Results: In the modelling experiment, the percentage decrease in PNa and PCl was similar in in vitro haemolysis, shear stress haemolysis, whole blood freeze–thaw haemolysis and packed cells freeze–thaw haemolysis and this was lower compared to the osmotic shock method. In the laboratory experiment, the change in PNa compared to the base pool was less ( p < 0.001) per unit increase in H-index in the freeze–thaw method (−0.33 mmol, 95% CI −0.35 to −0.31) compared to the osmotic shock method (−0.65 mmol, 95% CI −0.66 to −0.64). PCl did not change with haemolysis in the freeze–thaw method and changed by −0.21 ± 0.01 mmol per unit increase in the H-index in the osmotic shock method. Recovery of PNa and PCl increased with increasing H-index in both methods. Conclusion: The osmotic shock protocol is inappropriate for haemolysis studies because of dilution with DIW used for cell lysis. Recovery calculations may incorrectly compensate for genuine dilution caused by haemolysis.